CYCLONE 모델링 기법 개선을 통한 초고층 공사의 자재 양중 작업 프로세스 최적화 연구 - 황두원; 권오경; 최윤기; Hawng, Doowon; Kwon, Okyung; Choi, Yoonki (한국건설관리학회 논문집, 18(2), 2017)
The planning for material lifting operations is one of the key processes in high-rise building construction. Several previous studies have used rough calculations by referring to existing practices or establishing a target value for lifting cycle time or operating rate. Therefore, the purpose of this study is to propose a material lifting process optimization method for reducing the lifting cycle time and increasing the operating rate. In this study, we improve the cyclic operation network (CYCLONE) modeling method that considers the duration and zone information of each work task. This method can be used to hand over work tasks to another crew group in the work process. According to this methodology, this study optimizes the material lifting process, performs a sensitivity analysis, and evaluates the field applicability of the proposed material lifting process optimization method. Therefore, the optimized process was then applied to a high-rise building construction site. The lifting work process time and operating rate for the simulated as - is lifting process data, optimized process data, and field application result data were compared for each lifting height. From this comparison, the effectiveness of the optimization methodology was confirmed. 초고층 건축공사에서 리프트카를 이용한 자재 양중 관리는 핵심적인 관리분야 중 하나이다. 기존 연구들은 양중계획의 기본 단위인 양중 사이클타임이나 리프트카의 운행효율은 기존 사례를 참고하여 적용하거나 관리목표로 설정하고 개략적으로 산정하는 한계가 있었다. 따라서 본 연구에서는 양중 사이클타임을 단축하고 가동율을 향상시키기 위하여 자재 양중작업 프로세스를 최적화하는 방법론 제안을 목표로 하였다. CYCLONE 모델을 변형하여 작업시간과 작업위치를 반영할 수 있도록 개선하고, 세부 작업을 조정하여 프로세스를 최적화 하는 방법론을 제안하였다. 이 방법론에 따라 양중작업 프로세스를 개선하고 민감도 분석과 현장 적용성 평가를 실시하였으며 초고층 현장에 적용하였다. 기존 작업 프로세스와 개선된 작업 프로세스를 양중 높이별로 시뮬레이션하고 이를 현장 적용 결과 데이터와 비교하여 양중작업 시간 단축과 가동율 향상 정도를 비교 분석하여 최적화 방법론의 효용성을 검증하였다.